Brand Loyalty from a Consumer-Brand Relationship Perspective: An Empirical Study in the Vietnam Shampoo Market - Ly, Ngan Thuy (2004)
This dissertation explores three basic questions of brand loyalty: why and how brand loyalty is developed and what is the nature of it; from a consumer-brand relationship perspective. Eight consumers in Vietnamese shampoo market provide empirical data for a qualitative phenomenological study. Specifically, it argues that brand loyalty is a multifaceted phenomenon which can take the form of various types of brand-consumer relationship. It is originated with a process of exchanges between brands and consumers and primarily maintained by a self-connection that consumers feel with their brands.Building on the research findings, I put forward a number of conclusions. They address three concerns; practical (marketing), theoretical (consumer-brand relationship conceptual framework) and methodological (phenomenology study).